Intentional Excellence in the Baldwin Wallace University Neuroscience Program - Morris, Jacqueline K. (J Undergrad Neurosci Educ, 2015)
The Society for Neuroscience recognized Baldwin Wallace University’s (BWU) undergraduate Neuroscience program as their Program of the Year for 2012. This award acknowledged the “accomplishments of a neuroscience department or program for excellence in educating neuroscientists and providing innovative models to which other programs can aspire.” The Neuroscience program grew out of students interested in studying the biological basis of behavior. BWU’s neuroscience major is research-intensive, and all students are required to produce an empirically-based senior thesis. This requirement challenges program resources, and the demand for faculty attention is high. Thus, we developed an intentional 3-step peer mentoring system that encourages our students to collaborate with and learn from, not only faculty, but each other. Peer mentoring occurs in the curriculum, faculty research labs, and as students complete their senior theses. As the program has grown with over 80 current majors, we have developed a new Neuroscience Methods course to train students on the safety, ethics, and practice of research in the neuroscience laboratory space. Students in this course leave with the skills and knowledge to assist senior level students with their theses and to begin the process of developing their own projects in the laboratory. Further, our students indicate that their “peer mentorship was excellent,” “helped them gain confidence,” and “allowed them to be more successful in their research.”